2006
DOI: 10.1111/j.1365-2249.2006.03084.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic eosinophil response induced by respiratory syncytial virus

Abstract: SummaryRespiratory syncytial virus (RSV) is a common cause of lower respiratory tract disease (LRTD) in infants. Eosinophils have been suggested to play a role in the disease pathogenesis of LRTD. Inflammation can induce functional and morphological alterations of peripheral blood granulocytes. In patients with RSV LRTD, we aimed to investigate the eosinophil activation status by analysing surface markers. In vitro stimulation of eosinophils with cytokines leads to up-regulation of CD11b and priming markers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
1
24
0
4
Order By: Relevance
“…These results are also consistent with observations that eosinophils from infants with lower respiratory tract RSV disease demonstrated increased expression of CD11b. 38 Although ssRNA-induced CD11b expression was significantly reduced when MyD88-deficient eosinophils were used, the response was not entirely ablated. 39 These data suggest that ssRNA may operate through another as-yet unidentified recognition receptor, perhaps located in the cytosol and similar to those activated by dsRNA.…”
Section: Discussionmentioning
confidence: 99%
“…These results are also consistent with observations that eosinophils from infants with lower respiratory tract RSV disease demonstrated increased expression of CD11b. 38 Although ssRNA-induced CD11b expression was significantly reduced when MyD88-deficient eosinophils were used, the response was not entirely ablated. 39 These data suggest that ssRNA may operate through another as-yet unidentified recognition receptor, perhaps located in the cytosol and similar to those activated by dsRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological analysis showed that the dead infants had an extended peribronchiolitis and alveolitis, with infiltration by neutrophils and a few eosinophils (15)(16)(17). This problem can be reproduced in animal models, including mice and monkeys; when FI-RSV-immunized animals were challenged with RSV, there was extensive lung infiltration by neutrophils, lymphocytes, and some eosinophils, causing severe damage (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Despite this, we used PB eosinophils in these experiments since samples containing a sufficient amount of cells were easier to obtain and involved less discomfort for the subjects. In the first set of experiments, responsiveness to poly(I:C) was examined using expression of CD11b and secretion of IL-8 as representative indicators of activation [12, 23, 24]. R-837 (ligand for TLR7) was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%